2019
DOI: 10.1104/pp.18.01322
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Analysis Provides Insight into the Domestication and Improvement of Pear (P. pyrifolia) Fruit

Abstract: Knowledge of the genetic changes that occurred during the domestication and improvement of perennial trees at the RNA level is limited. Here, we used RNA sequencing analysis to compare representative sets of wild, landrace, and improved accessions of pear (Pyrus pyrifolia) to gain insight into the genetic changes associated with domestication and improvement. A close population relationship and similar nucleotide diversity was observed between the wild and landrace groups, whereas the improved group had substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…In contrast, the higher nucleotide diversity in NBS-encoding genes of cultivated groups in Europe might have occurred due to distinct selection pressure imposed by the cultivated habitats [41]. A recent study has shown that several regions with NBS-encoding genes had higher nucleotide diversity in landraces than the wild pear group [42]. The latter results, along with our findings, indicate that the genetic diversity of similar genes can be altered differently due to preferential selection of traits during independent domestication events as observed in pear [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the higher nucleotide diversity in NBS-encoding genes of cultivated groups in Europe might have occurred due to distinct selection pressure imposed by the cultivated habitats [41]. A recent study has shown that several regions with NBS-encoding genes had higher nucleotide diversity in landraces than the wild pear group [42]. The latter results, along with our findings, indicate that the genetic diversity of similar genes can be altered differently due to preferential selection of traits during independent domestication events as observed in pear [3].…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the expression of the NBS-encoding genes that have signatures of selection, four pear genotypes representing two cultivated and two wild accessions at three different fruit developmental stages (small, enlarged, and mature) were used. The RNAseq data of 12 samples were obtained from a previous study [42]. To investigate the expression changes of the NBS-encoding genes after inoculation with A. alternata, RNA-seq data of two pear species (P. calleryana and P. pyrifolia: 'Hongfen' pear) were used generated from previous study [19,20].…”
Section: Genome-wide Expression Analysis Of the Nbs-encoding Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…To solve this problem, many studies have been conducted on stone cells, and some progress has been made in revealing the biosynthetic and regulatory processes of pear stone cells and lignin [6, 39, 40]. However, the existing research has mainly concentrated on pear fruit after 15 DAP, and pear fruit in this period already contains a large number of stone cells [5, 41, 42]. The molecular mechanisms of stone cell formation and development in early fruit development (before 15 DAP) remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…These varieties are often used as pollen parents in Dangshan County, Anhui Province, China. Previous studies have shown that the 'Yali' has a high stone cell content, but the 'Cuiguan' has a low stone cell content [28,30]. However, the effect that the pollen parents with different stone cell levels have on the formation of stone cells in the fruit of 'Lianglizaosu' remains unknown.…”
Section: Introductionmentioning
confidence: 99%